Les partícules confirmatòries (com a question tags i com a respostes confirmatives) en català (amb especial referència al nord-occidental i al rossellonès) - Xavier Rull (Sintagma, 2023)
Questions can be open-ended (waiting for an affirmative or negative answer) but they can also have a confirmatory interpretation (i.e. there is an assumption that may be confirmed). In the latter case, question tags (like oh) may appear in the questions. This paper reports all the question tags in Catalan and the precise syntactic contexts in which they occur (at the beginning or at the end; although in principle they can all occur in two syntactic contexts, not all of them appear everywhere). Special emphasis is placed on the north-western dialects.